Politik Etnis Minoritas Partai Demokrasi Indonesia Perjuangan Di Kota Makaassar - Muh. Alif Fauzan Syah; Gustiana Kambo; Muhammad Imran Imran (Journal of Peace, Security and Democracy, 2026)
This study analyses the involvement of ethnic minorities within the structure and political activities of the Indonesian Democratic Party of Struggle (PDIP) in Makassar and examines the extent to which this nationalist party practices inclusive politics at the local level. A qualitative case study approach was employed to explore the dynamics of political representation in a multiethnic society. Data were collected through in-depth interviews with party officials, minority cadres, and community leaders, complemented by participatory observation and document analysis. The findings reveal that ethnic minority participation in PDIP Makassar is largely descriptive and symbolic, driven more by electoral strategy than by a genuine ideological commitment to pluralism. Nevertheless, minority cadres contribute to shaping the party’s image as an open nationalist institution and help expand its political base in multiethnic regions. These results reinforce Pitkin’s (1967) theory that substantive representation does not automatically arise from descriptive representation. Practically, this study highlights the need for more transparent recruitment mechanisms and inclusive internal policies to ensure that minority participation becomes equitable and sustainable within party structures and political decision-making processes.